2013
DOI: 10.1074/jbc.m113.483339
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin-Radixin-Moesin-binding Phosphoprotein 50 (EBP50) and Nuclear Factor-κB (NF-κB)

Abstract: Background: EBP50 is a scaffolding protein that is critical during vascular remodeling. Results: EBP50 expression is induced by inflammatory stimuli and potentiates NF-B activation and inflammation. Conclusion: EBP50 and NF-B participate in a feed-forward loop leading to increased macrophage activation and enhanced response of vascular cells to inflammation. Significance: This work reveals a novel mechanism regulating systemic and vascular inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…The levels of EBP50 expressed under these conditions were approximately three times higher than primary VSMC (Fig. 2D), and were similar to those observed under inflammatory conditions (27) and in vessels (23,24). Cells were incubated with FBS after overnight serum starvation to induce Akt activation (Fig.…”
Section: Skp2 Binds the Pdz1 Domain Of Ebp50 -Ebp50supporting
confidence: 73%
See 1 more Smart Citation
“…The levels of EBP50 expressed under these conditions were approximately three times higher than primary VSMC (Fig. 2D), and were similar to those observed under inflammatory conditions (27) and in vessels (23,24). Cells were incubated with FBS after overnight serum starvation to induce Akt activation (Fig.…”
Section: Skp2 Binds the Pdz1 Domain Of Ebp50 -Ebp50supporting
confidence: 73%
“…In addition to the effect on cell proliferation, EBP50 promotes VSMC motility (38) and the production of pro-inflammatory mediators in macrophages and of adhesion molecules in VSMC and endothelial cells (27). Collectively, these studies support the notion that EBP50 is a critical regulator of vascular remodeling.…”
Section: Ebp50 Stabilizes Skp2supporting
confidence: 58%
“…In addition, the recent study showed that the expression of NHERF1 was increased by nuclear transcription factor NF-κB in the primary macrophages and vascular smooth muscle cells [36]. In colon cancer cells, NHERF1 expression could be increased by the activation of NF-κB signaling and/or the multiple downstream signaling pathway of HIF-1α/VEGF-A induced in the hypoxia microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown various mechanisms of NHERF1’s involvement in NF-kB activation. For example, NHERF1 is a positive regulator of NF-kB activation in vascular inflammation by recruiting PKCζ at the cell membrane, resulting in activation of NF-kB [ 14 ]. NHERF1 maintains cyclic amino monophosphate (cAMP) and PKA signaling and regulates interleukin (IL)-6 production in human airway smooth muscle cells [ 15 ] and promotes mast cell activation via the C3a complement receptor (C3aR) pathway [ 16 ].…”
Section: Introductionmentioning
confidence: 99%